Dampak Modal Intelektual Hijau terhadap Pengungkapan Sukarela Emisi Karbon - Lin Oktris (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2018)
The purpose of this research is to analyze the effect of green intellectual capital on voluntary carbon emissions disclosure in IDX listed non financial companies in 2010-2014 with 40 companies samples. This research focuses on internal aspects side. This research methodology is multiple regression analysis. The results show that green intellectual capital have positive effect on voluntary carbon emissions disclosures. The results have contribution in disclosure of carbon emissions research for educators and stakeholders. The novelty of this research is to analyze new variables such as green intellectual capital. There are only 40 sample companiesbecause the disclosure of carbon emissions in Indonesia is still voluntary. Because samples only from Indonesia companies so the results cannot be generalized in ASEAN countries, Forfuture research, researcher can use primary data to measure green intellectual capital so that it reflects the perception of the company